PENERAPAN PEMBELAJARAN MENGGUNAKAN STRATEGI PCP UNTUK MENINGKATKAN MOTIVASI DAN HASIL BELAJAR BIOLOGI PADA MATERI JARINGAN TUMBUHAN DI KELAS XI IPA SMA NEGERI 4 AMBON - Marthinus Usmany (Biotik, 2019)
This study aims to improve students’ motivation and learning outcomes by PCP strategies on plant tissue material in class XI Science of SMA Negeri 4 Ambon. This research is a classroom action research design. The learning activities are divided into 2 cycles and refer to the John Elliot (1988) model which consists of four stages of action in each cycle. The results showed there was an increase in students’ motivation and learning outcomes from the first cycle to the second cycle, where student motivation reached 80% in the first cycle, and in the second cycle increased to 87%. The percentage of the students’ number who completed learning in the first cycle is 64%, that increased in the second cycle to 84%. The percentage increase of students’ motivation and learning outcomes has reached a success indicator so it can be concluded that the application of biology learning by using a PCP (Point Counter Point) strategy can increase the motivation and learning outcomes of students on plant tissue material of Class XI Science  in SMA Negeri 4 Ambon.